Family farming in Europe and Central Asia: History, characteristics, threats and potentials - Jan Douwe van der Ploeg (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
Most people have a clear understanding of what the term 'family farm' means. This is especially true in Europe. The term refers, in a seemingly straightforward and unambiguous way, to well-known and self-evident realities. It is solidly internalised in the memory of most people, even those with an urban background. People may like or dislike family farming, and scientists may dispute its virtues or shortcomings (Osaba 2014), but there is hardly any confusion or debate over the concept itself. [...]
Keywords: 330; family farming; Europe; Central Asia; history; characteristics; threats; potentials